2015
DOI: 10.1002/mds.26414
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Developments for Tics and Myoclonus

Abstract: Tics and myoclonus are phenomenologically similar given that both are jerk-like movements, but, in contrast to myoclonus, tics are often preceded by premonitory sensations and are typically associated with a variety of behavioral comorbidities, including attention deficit and obsessive-compulsive disorder. There are many other clinical features that help differentiate these two hyperkinetic disorders. Whereas behavioral and antidopaminergic therapies are most effective in the management of tics, clonazepam, ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 53 publications
(67 reference statements)
1
24
0
Order By: Relevance
“…The results from our study are similar to the treatment effects demonstrated with tetrabenazine,7–9, fluphenazine,29 topiramate,30 aripiprazole,31 and other drugs used to treat TS 1,4,32. Deutetrabenazine was well tolerated (the most common AEs were fatigue, headache, and irritability) and there were no serious AEs, such as depression.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results from our study are similar to the treatment effects demonstrated with tetrabenazine,7–9, fluphenazine,29 topiramate,30 aripiprazole,31 and other drugs used to treat TS 1,4,32. Deutetrabenazine was well tolerated (the most common AEs were fatigue, headache, and irritability) and there were no serious AEs, such as depression.…”
Section: Discussionsupporting
confidence: 82%
“…The pharmacological treatment of TS consists of antidopaminergic agents and a wide array of other psychotropic medications, and tolerability to these treatments is often compromised by the frequent occurrence of adverse effects (AEs) 3,4. Furthermore, a sizeable number of patients fail to obtain satisfactory relief with conventional medications, and some experience severe disabling tics requiring surgical intervention 5,6.…”
Section: Introductionmentioning
confidence: 99%
“…The subtle, but sometimes powerful, effect of deuteration has the potential to positively affect the safety, efficacy, and/or tolerability of drugs [17,19]. For example, SD-809, an analog of tetrabenazine with deuterated methoxy groups, forms an active metabolite that undergoes CYP2D6-mediated O-dealkylation at almost half the rate of the active metabolite of tetrabenazine, itself [20]. This provides a superior pharmacokinetic profile which has led to a New Drug Application (NDA) for SD-809 to the FDA for the treatment of chorea associated with Huntington's disease.…”
Section: Chemistrymentioning
confidence: 99%
“…Dr. Fahn helped to develop the Unified Myoclonus Rating Scale, still the only quantitative rating scale for this symptom . Depending on the cause or type of myoclonus, many treatments can ameliorate myoclonus, including clonazepam and other anticonvulsants, tetrabenazine, sodium oxybate, and botulinum toxin for segmental myoclonus …”
Section: Other Hyperkinetic Movement Disordersmentioning
confidence: 99%
“…Despite numerous genetic studies, no gene or genes responsible for Tourette syndrome and its behavioral co‐morbidities, particularly attention‐deficit hyperactivity disorder and obsessive‐compulsive behavior, have been identified . The treatment of Tourette syndrome must be tailored to the specific needs of the patient and includes behavioral therapy, presynaptic α 2 ‐adrenergic agonists, such as clonidine and guanfacine, anti‐dopaminergic drugs, such as tetrabenazine and fluphenazine, botulinum toxin injections, and deep brain stimulation …”
Section: Other Hyperkinetic Movement Disordersmentioning
confidence: 99%